Genetic parameters estimation and genome molecular marker identification for gestation length in pigs - Shi, Lijun; Li, Huihui; Wang, Lixian (Frontiers in Genetics, 2023)
Gestation length (GL) played an important role in piglet maturation of major organs and development of body, while the genetic molecular markers of GL had not been extensive identification. In this study, according to the 5,662 effective records of 3,072 sows, the heritability and repeatability of GL were estimated through the dmuai of DMU Version 6.5.1 with a repeatability model, namely, h^2 = 0.1594 and 〖re〗^2 = 0.2437. Among these sows, 906 individuals were genotyped with the GenSeek Genomic Profiler (GGP) Porcine 50K Chip and imputed to the genome-wide lever (9,212,179 SNPs) by the online software PHARP v1 for subsequent quality control and GWAS analyses. Further, the Fst was also performed to measure whether the actual frequency of genotypes in different GL phenotypes deviated from the theoretical proportion of genetic balance. We observed the highest degree of differentiation (average Fst value = 0.0376) in the group of 114 and 118 days, and identified a total of 1,002 SNPs strongly associated with GL. Through screening the genes located within a 500 kb distance on either side of the significant SNPs, we proposed 4,588 candidate genes. By the functional annotation, these candidates were found to be mainly involved in multicellular organism metabolism, early endosome, embryo implantation and development, and body and organ signaling pathway. Because of the simultaneous confirmation by GWAS and Fst analyses, there were 20 genes were replied to be the most promising candidates including HUNK, ARHGDIB, ERP27, RERG, NEDD9, TMEM170B, SCAF4, SOD1, TIAM1, ENSSSCG00000048838, ENSSSCG00000047227, EDN1, HIVEP1, ENSSSCG00000043944, LRATD1, ENSSSCG00000048577, ENSSSCG00000042932, ENSSSCG00000041405, ENSSSCG00000045589, and ADTRP. This study provided effective molecular information for the genetic improvement of GL in pigs.